2008
DOI: 10.1111/j.1365-2966.2007.12790.x
|View full text |Cite
|
Sign up to set email alerts
|

Reddening, colour and metallicity of the M31 globular cluster system

Abstract: Using metallicities from the literature, combined with the Revised Bologna Catalogue of photometric data for M31 clusters and cluster candidates [the latter of which is the most comprehensive catalogue of M31 clusters currently available, including 337 confirmed globular clusters (GCs) and 688 GC candidates], we determine 443 reddening values and intrinsic colours, and 209 metallicities for individual clusters without spectroscopic observations. This, the largest sample of M31 GCs presently available, is then … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
141
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(159 citation statements)
references
References 76 publications
(227 reference statements)
16
141
2
Order By: Relevance
“…3.2, shows that our E(B − V) estimates are on average about 0.03, 0.04 and 0.06 mag smaller than those by Barmby et al (2000), Fan et al (2008) and Caldwell et al (2011), respectively. The differences are within the combined errors of the quoted estimates with ours, and hence are hardly significant, but for the sake of completeness we can estimate how an offset of −0.05 mag in our reddening values would affect our results: the correction for such an offset would make our colours bluer by the same amount and our V 0 (HB) values brighter by ∼0.15 mag, thus shifting the overall metallicity distribution towards lower metallicities.…”
Section: The Assumed Reddeningmentioning
confidence: 90%
See 1 more Smart Citation
“…3.2, shows that our E(B − V) estimates are on average about 0.03, 0.04 and 0.06 mag smaller than those by Barmby et al (2000), Fan et al (2008) and Caldwell et al (2011), respectively. The differences are within the combined errors of the quoted estimates with ours, and hence are hardly significant, but for the sake of completeness we can estimate how an offset of −0.05 mag in our reddening values would affect our results: the correction for such an offset would make our colours bluer by the same amount and our V 0 (HB) values brighter by ∼0.15 mag, thus shifting the overall metallicity distribution towards lower metallicities.…”
Section: The Assumed Reddeningmentioning
confidence: 90%
“…More recent studies are those by i) Fan et al (2008), based on correlations between optical and infrared colours and metallicity, combined with the use of various reddening-free parameters (as in Barmby et al 2000); ii) Montalto et al (2009), based on a multiwavelength (far UV to IR) photometric study of dust properties; and iii) Caldwell et al (2011), based on 5 Å resolution spectra of target clusters compared to flux-calibrated spectra of reference clusters with similar metallicity that were dereddened using the Barmby et al (2000) values.…”
Section: Reddeningmentioning
confidence: 99%
“…Another widely used method to age-date extragalactic star clusters relies on multi-band photometry: the age can be derived from the spectral energy distributions (SED) measured in broad-band photometric systems, by comparing them with simple stellar population (SSP 3 ) synthesis models (e.g. Jiang et al 2003;Fan et al 2006Fan et al , 2008Fan et al , 2010Ma et al 2007Ma et al , 2009. Clearly, photometrybased technique are prone to errors owing to the uncertainty in the interstellar extinction, while spectral indices are virtually free from this effect.…”
Section: Introductionmentioning
confidence: 99%
“…Perrett et al (2002) suggest that the gradients is −0.017 and −0.015 dex arcmin −1 for the full sample and inner metal-poor clusters. More recently, Fan et al (2008) found that the slope is −0.006 and −0.007 dex arcmin −1 for the metal-poor subsample and whole sample while the slope approaches zero for the metal-rich subsample. Nevertheless, all these studies are based on GCs that are located relatively close to the center of the galaxy, usually at projected radii of less than 100 arcmin.…”
Section: Tablementioning
confidence: 99%
“…Ashman & Bird (1993); Barmby et al (2000); Perrett et al (2002) found the proportion of the metal-poor and metal-rich group is ∼ 2 : 1 to ∼ 3 : 1 with the peak positions of [Fe/H] ≈ −1.5 and −0.6, respectively. Fan et al (2008) examined the bimodality of metallicity distribution with a larger sample and the authors found the proportion is ∼ 1.5 : 1 and the the peak positions are [Fe/H] ∼ −1.7 and ∼ −0.7, respectively. However, the recent work of Caldwell et al (2011) suggests that there is no significant bimodality or trimodality for metallicity distribution with a sample of 322 M31 GCs, most of which have spectroscopic metallicity with high S/N ratio.…”
Section: Nomentioning
confidence: 99%